Специфіка управління власними доходами місцевих бюджетів в умовах фінансової децентралізації - Мартиненко, Валентина Віталіївна (Західноукраїнський національний університет, 2019)
В Україні, починаючи з 2014 р., реалізується реформа децентралізації, мета якої полягає у передачі частини владних повноважень центральних органів державної влади громадам. Оскільки у фінансовій сфері реформа децентралізації передбачає забезпечення фінансової автономії територіально-адміністративних одиниць, аналіз основних чинників впливу на управління власними доходами місцевих бюджетів набуває особливої актуальності. У статті досліджено специфіку та особливості управління власними доходами місцевих бюджетів України в умовах фінансової децентралізації. Основні методи дослідження, використані у статті: порівняльний аналіз – для ранжування власних надходжень зведених обласних бюджетів за обсягом; факторний аналіз – для ідентифікації та відбору факторів впливу на формування власних доходів місцевих бюджетів; регресійний аналіз – для формалізації впливу визначених факторів на динаміку власних доходів зведених обласних бюджетів. Обґрунтовано, що основу фінансової автономії громади в умовах фінансової децентралізації забезпечують широкі повноваження щодо управління формуванням власних надходжень до її бюджету. Встановлено, що у 2017 р. порівняно з 2014 р. власні доходи місцевих бюджетів України збільшилися в 2,3 рази, у тому числі як результат фінансової децентралізації. Доведено, що, проводячи децентралізацію управління власними доходами місцевих бюджетів, центральні органи державної влади, розширюючи фінансові повноваження адміністративно-територіальних одиниць, мають забезпечити зростання добробуту громадян, справедливість у регіональному розподілі доходів населення, сповільнення трудової імміграції.

Decentralization reform in Ukraine has been implemented since 2014. It aims at transferring some of the powers of central government to the communities. The reform of decentralization in the financial sphere should ensure the financial autonomy of territorial-administrative units. Therefore, the analysis of the main factors influencing the management of own revenues of local budgets is especially relevant. Research purpose is to investigate the specifics and features of managing the own revenues of local budgets of Ukraine under conditions of financial decentralization. Methods. Several research methods are used in the article. These are: comparative analysis – to rank own revenues of consolidated regional budgets by volume; factor analysis – to identify and select factors of influence on the formation of own revenues of local budgets; regression analysis – to formalize the influence of certain factors on the dynamics of own revenues of consolidated regional budgets. Results. It is proved that the basis of the community’s financial autonomy in the context of financial decentralization is provided by broad powers to manage the formation of its own revenues to its budget. It was established that in 2017 compared with 2014, own revenues of local budgets of Ukraine increased by 2.3 times, including as a result of financial decentralization. It is proved that, by decentralizing the management of own revenues of local budgets, central government bodies, expanding the financial powers of administrative-territorial units, should ensure the growth of citizens’ well-being, fairness in the regional distribution of incomes, and slowdown of labor immigration Conclusions. The obtained results make it possible to form the basis for the development of the main scenarios of forecasting the financial autonomy of the local budgets of Ukraine in their regional context. Further scientific researches of the author will be devoted to it.
Keywords: власні доходи; місцеві бюджети; органи місцевої влади; територіально-адміністративна одиниця; фіскальна політика; фінансова децентралізація; формалізація; own income; local budgets; local authorities; territorial-administrative unit; fiscal policy; financial decentralization; formalization